Pengaruh Model Pembelajaran Kooperatif Tipe Student Teams Achievement Division (STAD) Terhadap Hasil Belajar Siswa Pada Mata Pelajaran IPS kelas IV SD Negeri 095552 - Blau, Cindy Rizqy Utami; Sipayung, Larafika; Simanjuntak, Bernika; Damanik, Giovanni; Purba, Gusnily Mariani; Gaol, Reynaldi Lumban (Innovative: Journal Of Social Science Research, 2025)
The aim of this research is to determine the influence of the Student Teams Achievement Devision (STAD) type cooperative learning model on the learning outcomes of Grade IV SD. This research is a qualitative research using a One Group Pretest Posttest Design research design. The research sample was 18 students, in 1 class, namely class IV. The data collection used is test items. The data analysis used uses the N-Again test. Based on the research conclusions, there is an influence of the stad type cooperative learning model on the Indonesian language learning outcomes of students IV SD Negeri 095552.